Analysis of on-line survey about need for presence of higher education institutions on social networks: a step towards creation of communication strategy - Golubić, Kruno (2012)
The use of social networks among higher education institutions in Croatia is not widespread. An anonymous on-line survey about the importance of institutional presence on social networks was conducted during a ten-day period in May 2011 and included a questionnaire which was distributed to students and employees of two Zagreb based institutions. The results of the survey are interpreted and presented in this paper. These results can be used as a general guideline toward the creation of communication strategy for the presence of higher education institutions on web based social networks.